Application of Postpartum Exercise for the Prevention of Postpartum Complications Due to Immobilization - Natalia Debi Subani; Simon Sani Kleden; Adelinda Thein (Indonesian Journal of Global Health Research, 2022)
During the postpartum period, mothers are at risk of experiencing postpartum complications which are the main cause of maternal death in the world. Some of the things that trigger postpartum complications are postpartum bleeding, postpartum infections, urinary tract infections, uterine subinvolution, thrombophlebitis and pulmonary embolism and postpartum depression. The city of Kupang still has a high maternal mortality rate with the most common cause is bleeding which is a complication during childbirth. One of the programs that have been implemented to reduce maternal and child mortality is the KIA revolution and the Bakunase Community Health Center is one of those implementing the program. This health centre has a relatively high total number of visits for normal delivery and postpartum patients, so correct applicative measures are needed to prevent complications for postpartum mothers who undergo the delivery process here. Looking for the effect of postpartum exercise affects preventing complications in postpartum patients. This research uses a qualitative approach in the form of a descriptive case study. Results: An examination of the patient's general condition was carried out after the two activities above and the results were good and there were no signs of infection. Postpartum exercise affects preventing complications in postpartum patients so the application of good and regular postpartum exercise can increase the prevention of postpartum complications and can reduce maternal mortality due to bleeding which is still a major problem.